REVISITING THE LAHAD DATU STANDOFF IN SABAH: THE SECURITY ISSUES - Jelani Hamdan; Romzi Ationg; Kasim Mansur; Madiyem Layapan; Mohd. Sohaimi Esa (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This paper is revealing the key issue behind the Lahad Datu standoff that have significantly affected the life of Sabahans. The paper is intended not to blame anyone but instead to create awareness among us on the importance of strict international border controls, consistence citizenship policy, and transparent political activities. Such move is crucial as many Sabahan are of the opinion that the incident was strongly related with Malaysia’s internal political issues and the controversial citizenship-for-votes scandal. Accordingly, by applying a qualitative approach, this paper suggests that the policy makers impose strict international border controls, consistence citizenship policy, and transparent political activities.